ANALISIS SISTEM INFORMASI AKUNTANSI PEMBELIAN BAHAN BAKU SECARA TUNAI GUNA MENINGKATKAN EFEKTIVITAS PENGENDALIAN INTERN PADA PT. DWI MULYO LESTARI MADIUN - Fefi Wuri Ambarwati; Isharijadi Isharijadi (Assets: Jurnal Akuntansi dan Pendidikan, 2012)
This study evaluates the raw material purchasing system are applied in PT. Mulyo Dwi Lestari in order to enhance the effectiveness of internal control. The data was collected using interview and observation techniques. The analysis conducted is qualitative descriptive analysis. Based on the research that has been done, researchers can take the conclusion that the implementation of raw material purchasing system in the PT. Mulyo Dwi Lestari not support the effectiveness of internal control. The weaknesses include there isn’t form of purchase orders, goods receiving report form is not suitable with the basic principles of design, a dual function in the barn, yet numbered printed form, and never made a sudden inspection of the accounting records company's physical wealth.